Valence transition in topological Kondo insulator. (22nd October 2019) - Zhuang, Jia-Tao; Zheng, Xiao-Jun; Wang, Zhi-Yong; Ming, Xing; Li, Huan; Liu, Yu; Song, Hai-Feng
Abstract: We investigate the valence transition in three-dimensional topological Kondo insulator through slave-boson analysis of periodic Anderson model. By including the effect of intra-atomic Coulomb correlation between conduction and local electrons, we find a first-order valence transition from Kondo region to mixed valence state upon ascending of local f- level above a critical, and this valence transition usually occurs very close to or simultaneously with a topological transition. Near the parameter region of zero-temperature valence transition, rise of temperature can generate a thermal valence transition from mixed valence to Kondo region, accompanied by a first-order topological transition. Remarkably, above a critical which is considerably smaller than that generating paramagnetic valence transition, the original continuous antiferromagnetic transition is shifted to first order one, at which a discontinuous valence shift takes place. Upon increasing, the paramagnetic valence transition approaches then converges with the first-order antiferromagnetic transition, leaving a significant valence shift on the magnetic boundary. The continuous antiferromagnetic transition, first-order antiferromagnetic transition, paramagnetic valence transition and topological transitions are all summarized in a global phase diagram. Our proposed exotic transition processes can help to understand the thermal valence variation as well as the valence shift around the pressure-induced magnetic transition in topological Kondo insulator candidates and in other heavy-fermion systems.